Maternal Dietary Patterns and Preterm Delivery. Issue 2 (June 2015) - Englund-Ögge, L.; Brantsæter, A.L.; Sengpiel, V.; Haugen, M.; Birgisdottir, B.E.; Myhre, R.; Meltzer, H.M.; Jacobsson, B.
<x xml:space="preserve">Abstract</x> (BMJ. 2014;348:g1446)